SAT-LB077 Remission and Mortality Rates in Patients with Cushing Disease According to Their Tumor Size - Lam-Chung, Cesar (J Endocr Soc, 2019)
Objective It has been reported that Cushing’s disease due to macroadenoma is characterized by different biochemical features compared with microadenoma. We aimed to analyze and compare the clinical and biochemical features of patients with micro and macroadenomas causing Cushing disease. Methods We conducted a retrospective review of electronic and paper medical records that included 139 patients (108 microdenomas and 40 macroadenomas) with Cushing disease diagnosis who were studied and treated at the (undisclosed), in Mexico City from 2000 to 2017. Clinical characteristics, biochemical analysis of hypercorticolism, pituitary imaging findings, treatment modalities, remission as well as mortality rates were recorded. Results The mean age was 32.5 years (range 24-37) for microadenoma and 30.0 years (range 23-38) for macroadenoma (p=0.65). Female predominance was seen both in microadenoma (91.7%) and macroadenoma (87.1%) patients. Biochemical analysis of hypercortisolism including basal cortisol, ACTH, 24-hour urinary cortisol levels, and responsivity to low-dose dexamethasone suppression were similar between both groups. Remission and mortality rates after initial pituitary surgery for microadenoma and macroadenoma were 82.5 vs 17.5% (p=0.049) and 40.0% vs 60.0% (p=0.024), respectively. Using log-rank test we confirmed higher remission rates in microadenomas (p=0.049) and higher mortality risk with macroadenomas (p=0.024). Conclusion Our study suggest that patients with microadenomas showed better remission rates and lower mortality than those cases with macroadenomas, despite similar biochemical activity and treatment for CD. Therefore, further research is mandatory to identify those risk factors that gave different prognosis Reference Aydin, K & Dagdelen, S & Ozgen, Burce & Oruckaptan, H & Soylemezoglu, F & Erbas, T. (2014). Pituitary Corticotroph Microadenomas Versus Macroadenomas Causing Cushing’s Disease. Journal für Klinische Endokrinologie und Stoffwechsel. 7. 358-362. Keywords Cushing’s disease, corticotroph macroadenoma, corticotroph microadenoma Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.